Yb(OTf)3-Catalyzed Synthesis of Thiochromeno[2,3-b]chromenes and Their Antiproliferative Study - Mandal, Arnab; Singh, Satyajit; Daimary, Sajib; Arora, Arisha; Nambiar, Sujisha S.; Ghosh, Siddhartha S.; Khan, Abu Taleb (Synthesis, 2025)
The synthesis of hitherto unreported thiochromeno[2,3-b]chromenes from 4-hydroxy-2H-chromene-2-thiones was investigated with salicylaldehydes and cyclohexane-1,3-diones in the presence of 10 mol% Yb(OTf)3 in toluene. The three-component reaction proceeds via Knoevenagel condensation between the cyclohexane-1,3-dione and the salicylaldehyde followed by Michael addition with the 4-hydroxy-2H-chromene-2-thione. The products were obtained in good to excellent yields, with retention of the sulfur atom in the heterocycle. This synthetic approach offers a straightforward and reliable method for preparing sulfur-containing heterocycles, potentially expanding the scope of thiochromene chemistry. A molecular docking study was performed on the synthesized derivatives, and two compounds demonstrated a dose-dependent antiproliferative effect and enhanced ROS generation in the MDA-MB-468 triple-negative breast cancer cell line.
Keywords: 4-hydroxy-2H-chromene-2-thiones; thiochromeno[2,3-b]chromenes; Yb(OTf)3; linear products; cell viability; ROS detection